Hubungan Stigma Keluarga dengan Beban Caregiver dalam Merawat Pasien Gangguan Jiwa di Poliklinik Rumah Sakit Jiwa Provinsi Jambi - Yanti, Rahmi Dwi; Putri, Vevi Suryenti; Yesni, Marnila; Rahmadhani, Dwi Yunita; Pebrianti, Dwi Kartika; Yuliana, Yuliana (Universitas Baiturrahim, 2025)
Problems with mental disorders can occur from childhood, adolescence, adulthood and old age, if not handled or treated will cause severe mental disorders that cause decreased productivity and burden the family. Mental disorder is a chronic disease that requires a long process of healing. The process of recovery and healing in people with mental disorders requires family support to determine the success of the recovery. There is a negative stigma against ODGJ (People with Mental Disorders) and their families causing ODGJ and their families to be isolated. For the family, stigma will cause a heavy psychological burden so that it has an impact on the inadequate support provided by the family in the ODGJ recovery process. The purpose of this study was to determine the relationship between family stigma and caregiver burden in caring for patients with mental disorders at the mental hospital polyclinic in Jambi province. This research is a quantitative study with a correlation design using a cross sectional approach. This research was conducted at the Jambi Province RSJD Polyclinic in September 2022-August 2023. The population was 597 people and the sample was 60 people. The samples in this study were families of mental patients accompanying outpatients at the Mental Hospital in Jambi Province. The research sample was taken using a purposive technique. sampling, and data collection was carried out using instruments (Internalized Stigma Mental Illnes) and Zarit Burden Interview (ZBI). Data analysis with univariate and bivariate analysis with statistical tests using chi square. The results of the study were obtained from 60 patient families, 32 patient families (53.3%) with high stigma and 30 patient families (50.0%) with mild to moderate family burden. Chi square value (sig) 0.003 <α 0.05. So it can be concluded that there is a relationship between family stigma and caregiver burden in the Inpatient Room of the Rumah Sakit Jiwa Provinsi Jambi.